"Ecology and city: searching more sustainable urban models": Slogan of the XII Congreso Iberoamericano de Urbanismo (Salamanca 2006) (Ciudades, 2017)
"Ecology and city: searching more sustainable urban models".Slogan of the XII Congreso Iberoamericano de Urbanismo (Salamanca 2006)
Keywords: XII Congreso Iberoamericano de Urbanismo